Identification of upland cotton (Gossypium hirsutum) genotypes for acceptable fibre quality under biotic stress and recommended practices - AHUJA, S L; DHAYAL, L S (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2003 and 2004 under protected and unprotected environments to identify genotypes of upland cotton (Gossjpiltnr hirsnt~rmL .) for acceptable fibre quality norms made by CIRCOT in context to modem spinning and weaving mills requirements and niajor limiting factor to both cotton production and quality in India. During 2003, out of 142 genotypes, 15 in unprotected and 25 in protected environments were identified for acceptable fibre quality norms in unreplicated experiments, In replicated evaluation during 2004, 6 genotypes under unprotected environment 'CSH 3 1 18', 'CSH 31 I9', 'CSH 3 127, 'CSH 3 134', 'CSH 3 195' and 'CSH 3209' and 14 genotypes under protected environment; 'CSH 3002', 'CSH 3003', 'CSH 3005', 'CSH 3022', 'CSH 30311, 'CSH 3033', 'CSH 3047', 'CSH 3 127', 'CSH 3 132', 'CSH 3 167', 'CSH 3 18 1 ', 'CSH 3 183', 'CSH 3 185' and 'CSH 3 194' did not show much variation for fibre strength in the 2 years experiments. These genotypes had significantly higher fibre strength and length in comparison to check varieties and were with low infestation by jassids and low damage by bollworms. 'CSH 3 127' was the only genotype which had acceptable fibre properties under protected as well as unprotected environment. These genotypes can be further used for development of varieties for acceptable fibre quality.